Structural constants of the internal logic of tennis - Moreno, M. (Coaching and Sport Science Review, 2021)
This article discusses the factors that determine the structure of the sport of tennis based on the theories of motor action. It outlines a framework of tennis by reviewing the major theoretical contributions published and by identifying the most unique and specific elements of the game that every coach or athletic trainer needs to know when teaching the tennis concepts or planning and optimizing its training.